P27kip1 regulates the apoptotic response of gastric epithelial cells to Helicobacter pylori. Issue 6 (11th May 2004) - Eguchi, H; Carpentier, S; Kim, S S; Moss, S F
Abstract : Background: Helicobacter pylori infection increases the risk of gastric cancer but the molecular mechanisms responsible are not well understood. Gastric cells chronically exposed to H pylori in vitro develop resistance to apoptosis associated with low levels of p27, a cyclin dependent kinase inhibitor and haplo insufficient tumour suppressor gene that is downregulated in gastric cancer. Aim: To determine whether the low level of p27 protein is responsible for the resistance to apoptosis of gastric cancer cells. Methods: The effects of increasing the expression of p27 protein were examined by transiently and stably transfecting a plasmid encoding full length p27 mRNA into apoptosis resistant gastric cancer cell lines with low p27 expression that were derived from AGS gastric cancer cells by chronic H pylori coculture followed by dilutional cloning. Results: Low p27 expression in the apoptosis resistant derivative cell lines was associated with an approximate 30% decrease in p27 mRNA and an 80% decrease in p27 protein that was not due to increased proteasome dependent degradation of p27 protein. Transient or stable transfection with p27 constructs partially restored the sensitivity of the apoptosis resistant cells to 5-fluorouracil and H pylori induced apoptosis without altering spontaneous apoptotic cell death. Conclusions: These results demonstrate that p27 positively regulates, at least in part, the apoptotic response of gastric epithelial cells to H pylori . Low gastric p27 may promote gastric carcinogenesis associated with H pylori infection by inhibiting apoptotic pathways.